2004
DOI: 10.1063/1.1773367
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of hydrogen-induced exfoliation of InP

Abstract: To investigate the mechanisms of hydrogen-induced blistering in III–V materials, a standard splitting dose of 5×1016H2+∕cm2 at 150keV was implanted into InP substrates cooled to −20°C. Substrate cooling during the implantation improved the reproducibility of this approach by limiting hydrogen mobility during ion implantation. The implant profile and defect structure of unbonded wafers were studied for various annealing schedules with double-axis x-ray diffraction and transmission electron microscopy. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 12 publications
6
69
0
Order By: Relevance
“…Indeed, it was only recently shown that the concept of hydrogen-induced exfoliation can be applied to the transfer of thin films of InP and GaAs to foreign substrates. [6][7][8] Moreover, a detailed understanding of the role of H in these materials is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was only recently shown that the concept of hydrogen-induced exfoliation can be applied to the transfer of thin films of InP and GaAs to foreign substrates. [6][7][8] Moreover, a detailed understanding of the role of H in these materials is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Wafer bonding and layer transfer has now been applied to semiconductors other than silicon such as Ge, InP, GaAs, and GaN. [2][3][4][5][6] The mechanism of H-induced exfoliation has been extensively studied in the case of silicon, 7,8 and, more recently, in the case of InP. 9 The early work of Weldon et al provided important conclusions: ͑i͒ implantation induced defects serve to trap H within the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic of the layer transfer process which is involves ion implantation, direct wafer bonding and splitting of wafer induced by annealing. (Hayashi et al, 2004).…”
Section: Ionmentioning
confidence: 99%
“…A few years later, Hayashi et al presented an investigation of hydrogen implanted InP to obtain exfoliation (Hayashi et al, 2004). InP wafers were cooled to below room temperature (-20 °C) during implantation to assess blistering kinetics without any uncontrolled temperature excursions that may occur from the implantation process.…”
Section: Strain In Inp: Temperature and Dose Dependencementioning
confidence: 99%